2019
DOI: 10.1136/bmjspcare-2018-001704
|View full text |Cite
|
Sign up to set email alerts
|

Psycho-oncology care in breast cancer centres: a nationwide survey

Abstract: ObjectiveTo describe psycho-oncological care structures and processes in German breast cancer centres from the perspective of the centre administration.MethodsThe findings are based on a postal survey of a representative random sample of surgical sites of certified breast cancer centres in Germany. Data were collected in 2013 and 2014. The questionnaire included questions about infrastructure, patient information standards, psycho-oncological services and aspects of organisational culture. Data analyses includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Trevino et al showed that only 24.6 % of BC patients stage 0-III with anxiety received psychological counseling during adjuvant treatment in New York [14]. Another German survey determined a provision of psycho-oncological care in 86.8 % of all cases [15].…”
Section: Discussionmentioning
confidence: 99%
“…Trevino et al showed that only 24.6 % of BC patients stage 0-III with anxiety received psychological counseling during adjuvant treatment in New York [14]. Another German survey determined a provision of psycho-oncological care in 86.8 % of all cases [15].…”
Section: Discussionmentioning
confidence: 99%
“…In the routine practice of health professionals, these psychological problems must be assessed by using appropriate tools, such as HADS. Numerous publications [ 68 – 75 ] have also highlighted the importance of nursing practices, not only in assessing psychological states but also in implementing psychological interventions.…”
Section: Discussionmentioning
confidence: 99%
“…While 20-70% women who survived breast cancer need psychological support and the prevalence of anxiety and depression in this patient group is very high, a survey showed that 13% of participating German breast cancer centers are not offering psycho-oncological support by permanent employees. [47][48][49] Comparing the ZIGG program with other integrative oncology programs in Germany breast and gynecological cancer centers you will find some differences. At Klinikum Essen-Mitte, the integrative oncology program is offered within a cooperation of the Breast Center and the Department of Internal and Integrative Medicine.…”
Section: Discussionmentioning
confidence: 99%
“…While 20-70% women who survived breast cancer need psychological support and the prevalence of anxiety and depression in this patient group is very high, a survey showed that 13% of participating German breast cancer centers are not offering psycho-oncological support by permanent employees. 47 - 49 …”
Section: Discussionmentioning
confidence: 99%